Effects of Acute Administration of Corticosteroids during Mechanical Ventilation on Rat Diaphragm - Maes, Karen (American Thoracic Society, 2008)
Rationale: Mechanical ventilation is known to induce ventilator-induced diaphragm dysfunction. Patients submitted to mechanical ventilation often receive massive doses of corticosteroids that may cause further deterioration of diaphragm function. Objectives: To examine whether the combination of 24 hours of controlled mechanical ventilation with corticosteroid administration would exacerbate ventilator-induced diaphragm dysfunction. Methods: Rats were randomly assigned to a group submitted to 24 hours of controlled mechanical ventilation receiving an intramuscular injection of saline or 80 mg/kg methylprednisolone, a group submitted to 24 hours of spontaneous breathing receiving saline, or methylprednisolone and a control group. Measurements and Main Results: The diaphragm force–frequency curve was shifted downward in the mechanical ventilation group, but this deleterious effect was prevented when corticosteroids were administered. Diaphragm cross-sectional area of type I fibers was similarly decreased in both mechanical ventilation groups while atrophy of type IIx/b fibers was attenuated after corticosteroid administration. The mechanical ventilation-induced reduction in diaphragm MyoD and myogenin protein expression was attenuated after corticosteroids. Plasma cytokine levels were unchanged while diaphragm lipid hydroperoxides were similarly increased in both mechanical ventilation groups. Diaphragmatic calpain activity was significantly increased in the mechanical ventilation group, but calpain activation was abated with corticosteroid administration. Inverse correlations were found between calpain activity and diaphragm force. Conclusions: A single high dose of methylprednisolone combined with controlled mechanical ventilation protected diaphragm function from the deleterious effects of controlled mechanical ventilation. Inhibition of the calpain system is most likely the mechanism by which corticosteroids induce this protective effect.